2007
DOI: 10.1111/j.1439-0469.2006.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA coding region sequences support the phylogenetic distinction of two Indian wolf species

Abstract: Two small endangered populations of Indian wolves were recently shown to be distant from other wolf and dog mtDNA lineages characterized so far. None of the inner branches in the tree of canid species based on partial hypervariable D-loop sequences were, however, statistically supported by the data raising the question whether the two Indian wolf lineages represent two new species, occupying an intermediate position betweenCanis latrans and C. lupus or have diverged from the sub-species of C. lupus due to isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
97
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(112 citation statements)
references
References 22 publications
(70 reference statements)
14
97
1
Order By: Relevance
“…It is supported the morphological determination that two samples are not belongs to references species (Aggarwal et al, 2007). It is also supported a previous research which reported that Ijem belongs to Trachypithecus auratus mauritius while Embun is belongs to Trachypithecus auratus auratus based on Cyt-b sequence (Sakti, 2011).…”
Section: Resultssupporting
confidence: 74%
“…It is supported the morphological determination that two samples are not belongs to references species (Aggarwal et al, 2007). It is also supported a previous research which reported that Ijem belongs to Trachypithecus auratus mauritius while Embun is belongs to Trachypithecus auratus auratus based on Cyt-b sequence (Sakti, 2011).…”
Section: Resultssupporting
confidence: 74%
“…gov/Genebank) and published in Parra et al [14], Vila et al [18], Björnerfeldt et al [19], Aggarwal et al [20], Pilot et al [21], and Bekaert et al [22]. Bayesian tree was constructed using the MrBayes program [23].…”
Section: Methodsmentioning
confidence: 99%
“…We genotyped 29 autosomal microsatellite loci: 20,109,123,173,204,225,250,2001,2010,2054,2088,2137,2140,2159,2168, 2201, AHT002, AHT004, AHT101, AHT106, AHT126, AHT124, AHT133, AHT138, AHT119, AHT121, AHT136, AHT103, AHT125 [25][26][27][28][29]. Genotyping was performed using ABI3730XL (Uppsala Genome Center) and fragment analysis was done using GeneMapper 3.0 (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted, however, that the Holarctic grey wolf might not be a single species. Some wolf lineages, e.g., in India and North America may deserve species status as well [40][41][42].…”
Section: History Of the African Wolfmentioning
confidence: 99%